2013
DOI: 10.1103/physrevb.88.245112
|View full text |Cite
|
Sign up to set email alerts
|

ARPES study of the effect of Cu substitution on the electronic structure of NaFeAs

Abstract: Using high-resolution angle-resolved photoemission spectroscopy, we studied the electronic structure of NaFe 1−x Cu x As (x = 0.019,0.045,0.14). With increasing the doping concentration, we found that the Cu dopant introduces extra charge carriers. The overall band dispersions barely change with doping, suggesting that the Cu substitution does not affect local correlations. Similar to the case of NaFe 1−x Co x As, one electron pocket emerges at the Brillouin zone center at high doping levels. Moreover, the nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
1
28
2
Order By: Relevance
“…That means the decrease in the hole pocket size is relatively low compared to the increase in the electron pocket. This observation is not supporting the experimental [19][20][21][22][23]25,30,31] and theoretical [17,24,62] reports on weakly correlated 122-type and 111-type compounds, which suggests that in going from the substitution of Co to Ni to Cu to Zn in the place of Fe, the volume of the Fermi sheets increases and decreases, which is qualitatively consistent with the rigid-band model.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…That means the decrease in the hole pocket size is relatively low compared to the increase in the electron pocket. This observation is not supporting the experimental [19][20][21][22][23]25,30,31] and theoretical [17,24,62] reports on weakly correlated 122-type and 111-type compounds, which suggests that in going from the substitution of Co to Ni to Cu to Zn in the place of Fe, the volume of the Fermi sheets increases and decreases, which is qualitatively consistent with the rigid-band model.…”
Section: Discussioncontrasting
confidence: 42%
“…Many ARPES studies, dealing with the effect of impurities on the electronic structure, are available on weakly correlated 122-type [20][21][22][23]28] and 111-type [29][30][31] iron pnictides. Intriguingly, till now, no ARPES study has been made on the more correlated charge doped 11-type iron chalcogenides, which motivated us for the present study, though there are transport [32][33][34][35], thermal [36], and magnetic measurements [37] reporting on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the occupancy increases with increasing x in the electron doping region with u=5.4 eV. The ARPES experiment on NaFeAs 17 indicates that the total number of electron carriers introduced by Cu atoms increases when the Cu substitution increases from 0.019 to 0.14. However, the average number of electrons in Cu atom decreases significantly from 1.9 to 0.64 with increasing doping concentration.…”
Section: 54mentioning
confidence: 99%
“…16 Such an observation was also supported by the ARPES study, which exhibited the increasing of the Fermi level in NaFe 1−x Cu x As, indicating a fraction of electron doping introduced by the Cu dopant. 17 Up to date, the dispute on the electron or hole doping in the 111 and 122 phases is far from resolved. Therefore, further investigations are needed to explain the reason why the Cu substitution plays different roles in NaFe 1−x Cu x As and Ba(Fe 1−x Cu x ) 2 As 2 compounds.…”
Section: -15mentioning
confidence: 99%
“…x Cu x As with x up to 0.14 showed that, except for introducing extra charge carriers, the overall band dispersion barely changes with Cu doping, and the Fermi surface and/or all the energy bands near E F are dominated by Fe 3d orbitals [35]. It is of high interest to reveal the momentum-resolved electronic structure with ARPES in order to get further insight into the evolution of the Cu 3d-derived electronic states at or near E F , as the long-range AFM-ordered insulator evolves into a metallic or superconducting state with decreasing the concentration of the Cu dopant in NaFe 1-…”
mentioning
confidence: 99%